Deprescribing potential of commonly used medications among community-dwelling older adults: insights from a pharmacist's geriatric assessment - Bužančić, Iva; Držaić, Margita; Kummer, Ingrid; Ortner Hadžiabdić, Maja; Brkić, Jovana; Fialová, Daniela (Scientific reports, 2024)
Pharmacist's geriatric assessment can provide valuable insights into potential deprescribing targets, while including important information on various health-related domains. Data collected from a geriatric assessment questionnaire, for 388 patients, from the Croatian cohort of the EuroAgeism H2020 ESR 7 international project, along with guideline-based deprescribing criteria, were used to analyse potentially inappropriate prescribing of four medication groups (benzodiazepines (BZN), proton pump inhibitors (PPI), opioids, and non-steroidal anti-inflammatory drugs (NSAID)), and to assess the deprescribing potential. Binary logistic regression was used to explore the effects of age, gender, number of medicines and diagnoses, self-reported health, frailty score, and healthcare utilization on the likelihood of needing deprescribing. More than half of participants (n = 216, 55.2%) are candidates for deprescribing, with 31.1% of PPI, 74.8% of NSAID, 75% of opioid, and 96.1% of BZN users meeting at least one criterion. Most common criteria for deprescribing were inappropriately long use and safety concerns. Women (aOR = 2.58; p < 0.001), those reporting poor self-reported health (aOR = 5.14; p < 0.001), and those exposed to polypharmacy (aOR = 1.29; p < 0.001) had higher odds of needing to have medicines deprescribed. The high rate of deprescribing potential warrants prompt action to increase patient safety and decrease polypharmacy. Pharmacist's geriatric assessment and deprescribing-focused medication review could be used to lead a personalised approach.
Keywords: Deprescriptions; Humans; nevhodné předepisování; farmaceuti; Female; Aged; depreskripce; senioři; lidé; Geriatric Assessment; Geriatric assessment; Polypharmacy; Anti-Inflammatory Agents, Non-Steroidal; antiflogistika nesteroidní; Deprescribing; Geriatrics; samostatný způsob života; ženské pohlaví; Pharmacists; Independent Living; Inappropriate Prescribing; geriatrické hodnocení; Healthy ageing